Predictors of depression among the elderly persons with disabilities in Indonesia - The Maria M. Widagdo; Bernadeta D Widyaningsih; Setywanty Layuklinggi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Depression is a major mental problem in the elderly, particularly those with disability. This study's aim was to identify variables that predict depression in the elderly with disabilities. MATERIALS AND METHODS: This cross-sectional study was conducted in Gunungkidul Regency and Yogyakarta City from April to June 2021. The study participants were community-dwelling elderly aged 60 years and above with disabilities, who could communicate verbally without any apparent cognitive impairment. Data was collected by interviewing participants using structured questionnaire on following sections: Demographic characteristics, Mini-Mental State Examination (MMSE), Washington Group Short Set (WG-SS), Barthel Index of activities of daily living (ADL), Lawton Instrumental ADL (IADL) Scale, and Geriatric Depression Scale-30 (GDS-30). Multivariate linear regression analysis applied to identify variables significantly correlated with depression. Multinomial logistic regression analysis performed to obtain the odds ratio (OR). RESULTS: Study included 115 elderly persons with disabilities. Most of them had mobility impairment. Higher independence in ADL and being married were related with lower risk of depression, whereas increased age at disability increased the risk of depression (P = 0.001). The elderly who had greater independence with daily activities were less likely to have depression (OR = 0.639 for mild depression and OR = 0.589 for severe depression). Those who were not married were more likely to have mild depression (OR = 3.203) and severe depression (OR = 29.119). compared to the married elderly. Age at acquiring disability was associated with higher risk for mild depression (OR = 1.025) and severe depression (OR = 1.053). Higher independence in ADL and being married were related with lower risk of depression, whereas increased age at disability increased the risk of depression (P = 0.001). CONCLUSION: Independence in the ADL, being married, and being disabled as a young adult are negative predictors of depression in the elderly with disability.